The Influence Of Free Cash Flow, Profitability, Managerial Ownership, Institutional Ownership And Company Size On Debt Policy (Empirical Study Of Manufacturing Companies In The Consumer Goods Industry Sector Listed On The Indonesian Stock Exchange 2015-2019) - ANGGRAENI, Lisna; MINANARI, Minanari; YESSIE, Afly; INDRIAWATI, Fitri (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine the influence of free cash flow, profitability, managerial ownership, institutional ownership and company size on debt policy. The type of research used is quantitative research with a causal approach. In this research, the sampling method was carried out using a purposive sampling method. There were 28 manufacturing companies in the consumer goods industry sector in 2015-2019, which were used as samples in this research. This research uses secondary data taken from annual reports and company audit reports. The analysis method uses multiple linear regression analysis. The results of this study show that free cash flow has a negative and significant effect on debt policy, profitability has a positive and significant effect on debt policy, managerial ownership has a negative and significant effect on debt policy, institutional ownership has a negative and significant effect on debt policy, and company size has an effect and is not significant. Significant to debt policy.